The Impact of Using Duolingo in Enhancing Arabic Vocabulary Retention for Junior High School Students in Indonesia: في ترقية حفظ المفردات لطلاب الثانوية بإندونيسيا "Duolingo" تأثير اسخدام وسائط - Safoni Idris, Muhammad; Widia Nita Kasih, Baiq; Suparmanto (Journal of Arabic Language Learning and Teaching (JALLT), 2023)
Numerous studies suggest that teaching vocabulary poses challenges due to teachers' uncertainty about effective methods. Based on six years of academic experience at Slavaring Islamic School, difficulties in vocabulary learning stem from students' inability to apply vocabulary in conversations and a lack of classroom concentration, often exacerbated by negative learning experiences. To address this, multimedia, including text, audio, and video, is proposed to make vocabulary learning enjoyable. Duolingo, an educational program encompassing various activities like listening, reading, writing, and grammar, is highlighted as a valuable tool for vocabulary teaching. This research adopts a quasi-experimental design involving eighth-grade students at Slavaring Islamic Senior High School. The experimental group, taught using Duolingo, demonstrated enhanced vocabulary retention compared to the control group. Empirical evidence, obtained through multiple-choice tests and pre-tests, indicates a positive impact of Duolingo on vocabulary acquisition. Statistical analysis with a 5% significance level affirms the effectiveness of Duolingo, showcasing its potential to enhance vocabulary learning for eighth-grade students at Slavaring Islamic Junior High School in the academic year 2023/2024.